DESIGN GAP ANALYSIS OF EPILEPSY SEIZURE ALERT MOBILE APPLICATIONS FOR BYSTANDER SUPPORT - Nadira Anggrika Firdaus; Andreas Rio Adriyanto; Maria Josef Retno Budi Wahyuni (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2026)
Seizure alert mobile applications were created as a solution to improve emergency response for People With Epilepsy (PWE). However, existing applications mostly focus on notifying remote caregivers, leaving a critical gap in on-site bystander support. This study presents a comparative analysis and design gap identification of four seizure alert mobile applications, such as Aura: Seizure First Aid, Epicentr, SeizAlarm, and SeizureAlert – MyMedicWatch from the perspectives of both primary users (PWE) and secondary users (bystanders as helpers). Using a feature comparisons framework grounded in Human-Computer Interaction (HCI) principles, this study identifies the design gaps across activation method, user focus, interaction output, and bystander guidance. Findings reveal that even though Epicentr, SeizAlarm, and SeizureAlert have adopted automatic heart rate-based activation, none provides guidance for bystanders, making PWE face the challenges of not being able to get proper help during a seizure. Aura: Seizure First Aid is the only app focused on bystander guidance during the critical five minutes yet remains limited by its dependence on manual activation by the PWE. This study concludes that the integration of automatic seizure detection with on-site bystander guidance represents the most critical unaddressed design gap in current seizure alert application development.